Preparation and study as positive electrode of Li0.33La0.56TiO3-PANI nanocomposite - Milian, C. R.; Mosqueda, Y.; Aranda, P.; Varela, José Arana [UNESP]; Reguera, E.; Frutis, M. A.; Santoyo, J.; Perez-Cappe, E. (Maney Publishing, 2012)
A new electrode material based on the Li0.33La0.56TiO3-polyaniline nanocomposite is reported. This material is prepared by in situ polymerisation of aniline in the presence of Li0.33La0.56TiO3 nanoparticles. The nanocomposite and its precursors are characterised by X-ray diffraction, thermogravimetry, Fourier transform infrared, TEM, SEM, electrical conductivities and electrochemical measurements. The structural and electrochemistry study reveals the existence of relatively strong interactions between the conducting polymer and the oxide particles to assure good synergy in the transport process. The dc and ac electrical conductivities and diffusion coefficient measurements at room temperature indicate that the conductivity values are several orders of magnitude higher in the composite than in the oxide alone. This behaviour determines better reversibility for Li insertion in charge-discharge cycles compared to the pristine oxide and polymer when it is used as electrode of lithium batteries.
Keywords: Li0.33La0.56TiO3; PANI; Organic-inorganic nanocomposites; Electrode materials; Lithium batteries